The evolution and hybridization of reportage: characteristics of the genre in «La Vanguardia» and «ABC» (1982-2018) - Palau-Sampio, Dolors; Cuartero-Naranjo, Antonio (Universidad de Navarra, 2022)
The article herein presents the results of a research study focused on the evolution of reportage in the Spanish press over a span of four decades. This is the first longitudinal study covering such an extensive period (1982-2018) with regard to this narrative journalistic genre, through publications in La Vanguardia and ABC, the two oldest national newspapers in Spain. The aim of the study is to discover how the genre has evolved in recent decades, in terms of authorship, length, section in which it is published, headlines, visual and complementary elements, and the degree of hybridisation with other journalistic genres. Based on a quantitative and qualitative methodology, a sample was analysed using the constructed week sampling technique (N=346 issues). The results obtained show an increase in the amount and general length of the reports published from the year 2000 onward, as well as a tendency toward hybridisation with genres such as the crónica and the news report. However, there is no evidence of a commitment to narrative aspects. The increase in pagination has been fostered by the incorporation of visual and design elements, while the Society section continues to have the highest share of reportage pieces. Most of the reportage items analysed were by-lined by one person, who were predominantly men, which suggests a gender gap in the authorship of prestigious journalistic genres.
Keywords: Periódicos - España - 1982-2018; Reportage; Journalistic genre; Hybrid genres; Narrative journalism; Daily press